2019
DOI: 10.3389/fcimb.2019.00177
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Taurocholate Stimulates Campylobacter jejuni Outer Membrane Vesicle Production via Down-Regulation of the Maintenance of Lipid Asymmetry Pathway

Abstract: Campylobacter jejuni outer membrane vesicles (OMVs) contain numerous virulence-associated proteins including the cytolethal distending toxin and three serine proteases. As C. jejuni lacks the classical virulence-associated secretion systems of other enteric pathogens that deliver effectors directly into target cells, OMVs may have a particularly important role in virulence. C. jejuni OMV production is stimulated by the presence of physiological concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 54 publications
(91 reference statements)
3
37
0
1
Order By: Relevance
“…Most studies to date on membrane vesiculation have focused on Gram-negative bacteria (and hence, OMVs). However, recently there has been increasing interest in the regulatory role of the inner membrane ( Davies et al, 2019 ; Takaki et al, 2020 ). The role of inner membrane in outer membrane vesiculation could be considered via various aspects, including (I) Inner membrane regulates and keeps the cross-talk between the components of the bacterial envelope, e.g., outer membrane-peptidoglycan-inner membrane, (II) Inner membrane regulates the stress response-pathway, (III) Inner membrane contains maintenance elements for outer membrane asymmetry (IV) Inner membrane can convey the turgor pressure of misfolded proteins and SOS response-pathway to periplasm and outer membrane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies to date on membrane vesiculation have focused on Gram-negative bacteria (and hence, OMVs). However, recently there has been increasing interest in the regulatory role of the inner membrane ( Davies et al, 2019 ; Takaki et al, 2020 ). The role of inner membrane in outer membrane vesiculation could be considered via various aspects, including (I) Inner membrane regulates and keeps the cross-talk between the components of the bacterial envelope, e.g., outer membrane-peptidoglycan-inner membrane, (II) Inner membrane regulates the stress response-pathway, (III) Inner membrane contains maintenance elements for outer membrane asymmetry (IV) Inner membrane can convey the turgor pressure of misfolded proteins and SOS response-pathway to periplasm and outer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…(III) Inner membrane and envelope asymmetry. The inner membrane is a key element in the maintenance of the membrane lipid asymmetry (MLA) pathway regulating membrane vesiculation ( Davies et al, 2019 ). In the asymmetric outer membrane, the outer leaflet harbors lipopolysaccharides whereas the inner leaflet is mostly composed of phospholipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment with this bile salt, C. jejuni outer MV production increased, with increased MVs-associated proteolytic activity as a consequence. Recently, Davies et al [186] also showed that the production of MVs by C. jejuni is stimulated after addition of physiological concentrations of sodium taurocholate. In the host organism, bile salts are according to Stieger [187]: "A major constituent of bile and are secreted by hepatocytes into bile and delivered into the small intestine, where they assist in fat digestion."…”
Section: Gram Negative Bacteriamentioning
confidence: 99%
“…C. jejuni is able to modify the CCV to meet its metabolic needs and also interfere with the canonical endocytic pathway, preventing C. jejuni killing within lysosomes [6]. Outer membrane vehicles have also been explored which can act as cargo delivery vehicles, possibly containing and delivering virulence-related proteins [7].…”
Section: Key Features and Discoveriesmentioning
confidence: 99%